Volume Transmission of Substance P in Striatum Induced by Intraplantar Formalin Injection Attenuates Nociceptive Responses via Activation of the Neurokinin 1 Receptor - Yoki Nakamura; Hiroki Izumi; Takumi Shimizu; Kazue Hisaoka-Nakashima; Norimitsu Morioka; Yoshihiro Nakata (Elsevier, 2013)
Abstract.: To clarify a role of substance P (SP) in an endogenous pain control mechanism involving the rat striatum, striatal SP release was measured over time by microdialysis following intraplantar injection of 0.4% formalin. A slow-onset but significant increase of SP and neurokinin 1 receptor (NK1R) internalization in the contralateral striatum were observed following the second phase of formalin-induced nociceptive behaviors. Moreover, 60 min after formalin injection, preprotachykinin-A, the SP mRNA, and the immediate early gene cFOS were upregulated in the contralateral striatum. Continuous infusion of SP into the striatum by reverse microdialysis attenuated formalin-induced second phase, but not the first phase, nociceptive behaviors, and hind paw mechanical allodynia. Moreover, these anti-nociceptive effects of SP were completely inhibited by co-treatment with the NK1R antagonist CP96345. Acute microinjection of SP, however, at a dose that was similar to the total dose of SP continuously infused into the striatum, did not affect formalin-induced nociceptive behaviors. These data indicate that striatal NK1R activation leads to pain suppression rather than facilitation. Furthermore, volume transmission of SP in the striatum appears to be indispensable in the mechanism of pain control. Modulation of striatal NK1Rs could prove to be a useful method of inducing analgesia.[Supplementary Figure: available only at http://dx.doi.org/10.1254/jphs.12218FP] Keywords:: formalin, neurokinin 1 receptor, striatum, substance P, volume transmission